Pengaruh Jumlah Penduduk dan Upah Minimum Kota Terhadap Tingkat Pengangguran Terbuka di Pekanbaru tahun 2010-2017 - Herman Herman (STIE Mandala Jember, 2019)
The city of Pekanbaru has a population of 1,091,088 with a minimum wage of only Rp 2,557,486. This study aims to determine the effect of population and city minimum wages on the level of open unemployment in Pekanbaru in 2010- 2017. This research is a quantitative research, with data obtained from secondary data, namely from BPS Kota Pekanbaru in 2010-2017. Data analysis with multiple regression. The results of the study show that: 1) The population has a negative and significant effect on the level of open unemployment in Pekanbaru City 2010-2017. 2) the city minimum wage does not significantly influence the unemployment rate in Pekanbaru City 2010-2017. 3) the magnitude of the influence of the total population and the city of Pekanbaru's minimum wage on the unemployment rate of 50.2 percent.